Unknown Huichol: Shamans and Immortals, Allies against Chaos - Fikes, Jay Courtney (Rowman & Littlefield Publishers, 2010)
The culmination of 34 years of ethnographic fieldwork and archival research, this book offers ground-breaking insights into fundamental principles of Huichol shamanism and ritual. The scope and length of Fikes's research, combined with the depth of his participation with four Huichol shamans, enable him to convey with empathy details of shamanic initiation, methods for diagnosis and treatment of illness, and motives for performing funeral, deer and peyote hunting, and maize-cultivating rituals.